Peningkatan Produktivitas Melalui Penerapan 5S di IKM Kulit di Sleman, Yogyakarta - Suci Miranda; Elisa Kusrini (Universitas Islam Indonesia, 2021)
Small and Medium Enterprise (SME) called MARS Genuine Leather is one of the SMEs under the guidance of the Department of Industry and Trade (Disperindag) in the Sleman region, Yogyakarta. In 2018, MARS and 10 other SMEs in Sleman and Bantul Regency have involved in research with the Department of Industrial Engineering at the Islamic University of Indonesia regarding supply chain performance analysis using the Supply Chain Operation Reference (SCOR) Model. The results showed that MARS had the lowest supply chain value among the 5 SMEs in the Sleman region. Continuing the results of the research, improvements were made through Community Service activities regarding the implementation of 5S in MARS. the Department of Industry and Trade (Disperindag) of Sleman has provided several pieces of training on the implementation of 5S for SME owners. However, this training has not been applied directly to each IKM. Therefore, this service activity aims to provide hands-on training on the implementation of 5S at IKM MARS as well as one of the improvements that can be made to the results of previous supply chain performance analysis research. The results of this service are in the form of direct training guidance at IKM, videos of the first 3S implementation (Seiri, Seiso, Seiton), and a checklist form that can be used by IKM as an internal audit. The 5S knowledge and skills that have been applied in MARS are expected to help the enterprise to reduce waste as well as increase productivity in the future.